Models for releasing the lupus anticoagulant test - Jessica S. F. Abreu; Andreza O. Santos; Nelson Medeiros Jr; Christiane P. Gouvea (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: Thrombophilia is a thrombosis susceptibility of genetic, acquired or mixed nature. Among acquired causes, the antiphospholipid syndrome (APS) stands out as an autoimmune disease characterized by antiphospholipid antibodies, thrombotic events or recurrent gestational loss. Laboratory diagnosis is based on the detection of lupus anticoagulant (LAC), anti-β2-glycoprotein 1 and anticardiolipin; however the determination of LAC still demands uniformity. The last guideline published by the Clinical and Laboratory Standards Institute (CLSI) prioritizes the screening and confirmatory steps, to the detriment of the mixing phase. Objectives: To compare the forms of releasing the LAC and to adopt an investigation protocol in agreement with the international guidelines. Methods: Thirty-six samples with prolonged results in the screening step by the dilute Russell viper venom time (dRVVT) or activated partial thromboplastin time (APTT) were subjected to the mixing steps (1:1) and to the confirmatory steps with high concentrations of phospholipids. Results: For APTT, values whose indexes of circulating anticoagulant (ICA) were greater than 15% were considered positive. For dRVVT, the ratio between screening and confirmation was also used. Of the 36 tested samples, 14 showed correction in the mixing step, but only one resulted negative. Conclusion: ICA aided in identifying the weak antibodies that were probably diluted in the mixing step. There is no gold standard test for the diagnosis of APS, and LAC detection still requires standardization of technique and interpretation.